Antibacterial activity and GC-MS profile of secondary metabolites of Bacillus subtilis subsp. subtilis HSFI-9 associated with Holothuria scabra - MAYA DIAN RAKHMAWATIE; NANIK MARFU’ATI; BESTY BARSALIPUTRI; AIDA ZAKIYATUL FIKRIYAH; STALIS NORMA ETHICA (Society for Indonesian Biodiversity, 2023)
Abstract. Rakhmawatie MD, Marfu’ati N, Barsaliputri B, Fikriyah AZ, Ethica SN. 2023. Antibacterial activity and GC-MS profile of secondary metabolites of Bacillus subtilis subsp. subtilis HSFI-9 associated with Holothuria scabra. Biodiversitas 24: 2843-2849. The emergence of resistant bacteria has led to the importance of new antibacterial discovery. Before this research, the marine biota Holothuria scabra found in the Kodek gulf area, West Nusa Tenggara, Indonesia, was explored to isolate Bacillus sp. The present research was conducted to explore Bacillus sp. to produce secondary antibacterial metabolites, by culturing isolate using media containing starch, yeast, and peptone. Ethyl acetate was used for secondary metabolite extraction. Antibacterial activity screening was carried out by two-fold microdilution test to obtain Minimum Inhibitory Concentration (MIC) value. In this study, it was found that the ethyl acetate extract of the strain HSFI-9 can inhibit the growth of Staphylococcus aureus, Extended Spectrum ?-Lactamase (ES?L)-Escherichia coli, and Mycobacterium smegmatis with sequential minimum inhibitory concentrations (MIC) values ??of 3.125; 25; and 50 µg/mL. Based on phylogenetic tree analysis, the strain HSFI-9 show 99.71 similarity with Bacillus subtilis subsp. subtilis. The ethyl acetate extract of Bacillus subtilis subsp. subtilis HSFI-9 metabolomics profile was analyzed using Gas Chromatography-Mass Spectroscopy (GC-MS). It showed five volatile secondary metabolites, with the first dominant compound being (2S, 3S)-(-)-3-propyloxiranemethanol (MW 116, C6H12O2) with an area of ??34.78% (database similarity index of 73.3%). This study concluded that B. subtilis subsp. subtilis HSFI-9 could be further developed as an antibacterial producer.